Hop Extract: An Efficacious Antimicrobial and Anti-biofilm Agent Against Multidrug-Resistant Staphylococci Strains and Cutibacterium acnes - Di Lodovico, Silvia; Menghini, Luigi; Ferrante, Claudio; Recchia, Erica; Castro-Amorim, Juliana; Gameiro, Paula; Cellini, Luigina; Bessa, Lucinda J. (Frontiers in Microbiology, 2020)
Bacteria belonging to Staphylococcus genus, in particular methicillin-resistant S. aureus and multidrug-resistant S. epidermidis, together with Cutibacterium acnes are the main strains involved in skin disease. The increase of multidrug-resistant bacteria has revived attention on natural compounds as alternative agents for the treatment management. Among these, hop extract, a hydroalcoholic solution obtained from experimental crops of Humulus lupulus L. variety cascade (hop), displays diverse biological properties including an antimicrobial one. The aim of this study was to evaluate the antimicrobial activity and the capacity to inhibit the biofilm formation of a characterized hop extract against S. aureus and S. epidermidis multidrug-resistant strains, and against a C. acnes strain. The hop extract was characterized by i) phytochemical analysis through a reversed phase HPLC-fluorimetric method, ii) biocompatibility test with Artemia salina L., iii) cytotoxicity against two cell lines, iv) docking analysis and v) antimicrobial and anti-biofilm activities by detection of zones inhibition, MICs, biomass quantification and cell viability. The hop extract was biocompatible and non-cytotoxic at all tested concentrations. HPLC analysis revealed significant levels of gallic acid, resveratrol and rutin. This last compound was the most representative displaying a high affinity against PBP2a and KAS III (Ki values in the submicromolar range). The characterized hop extract showed a good antimicrobial action with MICs ranging from 1 to 16 g/ml and was able to inhibit the biofilm formation of all tested strains, except for two S. aureus strains. The biofilm formed in presence of the hop extract was significantly reduced in most cases, even when present at a concentration of ¼ MIC. The Live/Dead images showed a remarkable inhibition in the biofilm formation by hop extract with a weak killing action. Overall, the tested hop extract is a good candidate to further explore for its use in the prevention of infection particularly, by multidrug-resistant Gram-positive pathogens.